Positive electrode active material, lithium ion battery, and method for producing positive electrode active material

By exchanging Na of the Na containing oxide with P2 type structure into Li, heating and washing, the resistance of the positive electrode active material is reduced, and the problem of high resistance of the positive electrode active material in the prior art is solved, and the performance of the lithium-ion battery is improved.

CN119864411APending Publication Date: 2025-04-22TOYOTA JIDOSHA KK
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411038195.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-20
Filing Date
2024-07-31
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The existing positive electrode active material with O2 type structure still has room for improvement in resistance.

Method used

By exchanging at least a part of Na containing oxides of Na having a P2 type structure into Li, an oxide containing oxides of Li with an O2 type structure is obtained, and heating and washing on this basis are performed to reduce the amount of carbon and sulfur, thereby reducing the resistance.

Benefits of technology

The low resistance of the positive electrode active material is achieved and the performance of lithium-ion batteries is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864411A_ABST
    Figure CN119864411A_ABST
Patent Text Reader

Abstract

The invention relates to a positive electrode active material, a lithium ion battery, and a method for manufacturing the positive electrode active material. The positive electrode active material of the present disclosure has an O2-type structure and has a carbon content of 500 ppm or less. A method for producing a positive electrode active material according to the present disclosure includes: exchanging at least a portion of Na in an Na-containing oxide having a P2-type structure with Li to obtain an Li-containing oxide having an O2-type structure; and heating the Li-containing oxide to reduce the amount of carbon in the Li-containing oxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application discloses a positive electrode active material, a lithium ion battery, and a method for producing the positive electrode active material. Background Art

[0002] As the positive electrode active material, a positive electrode active material having an O2 type structure is known. As disclosed in Japanese Patent Application Laid-Open No. 2011-170994, a positive electrode active material having an O2 type structure can be obtained by exchanging at least a portion of Na in an oxide containing Na having a P2 type structure with Li. Summary of the invention

[0003] Conventional positive electrode active materials having an O2 type structure still have room for improvement in terms of resistance.

[0004] The present application discloses the following multiple solutions as means for solving the above-mentioned problems.

[0005] <Option 1>

[0006] The positive electrode active material is a positive electrode active material having an O2 type structure and has a carbon content of 500 ppm or less.

[0007] <Option 2>

[0008] The positive electrode active material according to claim 1, which has a sulfur content of 300 ppm or less.

[0009] <Option 3>

[0010] A lithium ion battery comprising a positive electrode active material layer, an electrolyte layer and a negative electrode active material layer, wherein the positive electrode active material layer comprises the positive electrode active material according to embodiment 1 or 2.

[0011] <Option 4>

[0012] A method for producing a positive electrode active material comprises: exchanging at least a portion of Na in a Na-containing oxide having a P2-type structure with Li to obtain a Li-containing oxide having an O2-type structure; and heating the Li-containing oxide to reduce the carbon content of the Li-containing oxide.

[0013] <Option 5>

[0014] The method for producing a positive electrode active material according to claim 4, wherein the atmosphere when the Li-containing oxide is heated is an inert gas atmosphere or an oxygen-containing atmosphere, and the temperature when the Li-containing oxide is heated is 200° C. to 300° C.

[0015] <Option 6>

[0016] The method for producing a positive electrode active material according to embodiment 4 or 5, comprising: washing the Li-containing oxide with water to reduce the amount of sulfur in the Li-containing oxide.

[0017] The positive electrode active material disclosed in the present invention has an O2 type structure and low resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Features, advantages, and technical and industrial significance of exemplary embodiments of the present invention will be described below with reference to the accompanying drawings, wherein like reference numerals represent like elements, and wherein:

[0019] Figure 1 An example of a flow of a method for producing a positive electrode active material having an O2 type structure is shown.

[0020] Figure 2 The mechanism of carbon removal by heating is schematically shown.

[0021] Figure 3 An example of the structure of a lithium ion battery is schematically shown. DETAILED DESCRIPTION

[0022] An embodiment of the positive electrode active material, lithium ion battery, and method for producing the positive electrode active material of the present disclosure is described below, but the positive electrode active material, lithium ion battery, and method for producing the positive electrode active material of the present disclosure are not limited to the embodiment described below.

[0023] 1. Positive active material

[0024] A positive electrode active material according to one embodiment has an O2 type structure and contains a carbon content of 500 ppm or less.

[0025] 1.1 Crystal structure

[0026] The positive active material involved in one embodiment has at least an O2-type structure (belonging to the space group P63mc) as a crystal structure. The positive active material involved in one embodiment may have a crystal structure other than the O2-type structure while having the O2-type structure. As a crystal structure other than the O2-type structure, for example, the T#2-type structure (belonging to the space group Cmca) formed when Li is separated from the O2-type structure and Li is inserted into the O2-type structure, and the O6-type structure (belonging to the space group R-3m, the c-axis length is 2.5nm or more and 3.5nm or less, typically 2.9nm or more and 3.0nm or less, and the O3-type structure belonging to the space group R-3m is different). The positive active material involved in one embodiment may have an O2-type structure as the main phase. The positive active material involved in one embodiment may have one or both of the T#2-type structure and the O6-type structure while having the O2-type structure. The crystal structure that becomes the main phase of the positive active material involved in one embodiment may change according to its charge and discharge state.

[0027] 1.2 Chemical composition

[0028] The chemical composition of the positive electrode active material involved in one embodiment is not particularly limited as long as it can maintain the above-mentioned O2 type structure. The positive electrode active material having an O2 type structure may contain at least one element of Mn, Ni and Co, Li and O as constituent elements. In the case where the positive electrode active material contains at least Li, Mn, one or both selected from Ni and Co, and O as constituent elements, in particular, in the case where it contains at least Li, Mn, Ni, Co, and O as constituent elements, it is easy to obtain higher performance. The positive electrode active material involved in one embodiment may have a structure consisting of Li a Na b Mn x-p Ni y-q Co z-r M p+q+rA chemical composition represented by O2 (wherein 0<a<1.00, 0≤b≤0.20, x+y+z=1, and 0≤p+q+r<0.17, and the element M is at least one selected from B, Mg, Al, K, Ca, Ti, V, Cr, Fe, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo and W). When the positive electrode active material has such a chemical composition, it is easy to maintain the O2 type structure. In the above chemical composition, a is greater than 0, and can be greater than 0.10, greater than 0.20, greater than 0.30, greater than 0.40, greater than 0.50 or greater than 0.60, and is less than 1.00, and can be less than 0.90, less than 0.80 or less than 0.70. In the above chemical composition, b is greater than 0, and can be greater than 0.01, greater than 0.02 or greater than 0.03, and is less than 0.20, and can be less than 0.15 or less than 0.10. In addition, x is 0 or more, and may be 0.10 or more, 0.20 or more, 0.30 or more, or 0.40 or more, and is 1.00 or less, and may be 0.90 or less, 0.80 or less, 0.70 or less, 0.60 or less, 0.50 or less, or 0.40 or less. In addition, y is 0 or more, and may be 0.10 or more, or 0.20 or more, and is 1.00 or less, and may be 0.90 or less, 0.80 or less, 0.70 or less, 0.60 or less, 0.50 or less, or 0.40 or less. In addition, z is 0 or more, and may be 0.10 or more, 0.20 or more, 0.30 or more, or 0.40 or more, and is 1.00 or less, and may be 0.90 or less, 0.80 or less, 0.70 or less, 0.60 or less, 0.50 or less, or 0.40 or less. Element M contributes less to charge and discharge. In this respect, in the above-mentioned chemical composition, by p+q+r being less than 0.17, it is easy to ensure a high charge and discharge capacity. p+q+r may be less than 0.16, less than 0.15, less than 0.14, less than 0.13, less than 0.12, less than 0.11 or less than 0.10. On the other hand, by including the element M, the O2 type structure is easily stabilized. In the above-mentioned chemical composition, p+q+r is greater than 0, and may be greater than 0.01, greater than 0.02, greater than 0.03, greater than 0.04, greater than 0.05, greater than 0.06, greater than 0.07, greater than 0.08, greater than 0.09 or greater than 0.10. The composition of O is approximately 2, and is not limited to exactly 2.0, and is variable.

[0029] 1.3 Carbon content

[0030] In the previous positive electrode active materials with O2 type structure, lithium carbonate is inevitably generated due to its manufacturing process, etc. Specifically, the positive electrode active material with O2 type structure can be obtained by replacing Na of the oxide containing Na with P2 type structure (ion exchange) with Li. Among them, Li or Li compounds that do not constitute O2 type structure inevitably remain on the surface of the positive electrode active material after ion exchange. In addition, O2 type structure is a quasi-stable phase, and Li or Li compounds can also be generated due to the collapse of a part of O2 type structure. Such Li or Li compound reacts with, for example, carbon dioxide from the atmosphere to become lithium carbonate. When the positive electrode active material with O2 type structure contains a large amount of lithium carbonate, the resistance of the positive electrode active material becomes large.

[0031] The positive electrode active material involved in one embodiment has a carbon content of less than 500ppm on a mass basis. That is, the positive electrode active material involved in one embodiment has a significantly less amount of lithium carbonate as an impurity than the previous positive electrode active material. Therefore, the positive electrode active material involved in one embodiment has a low resistance compared with the previous positive electrode active material. The carbon content of the positive electrode active material involved in one embodiment may be less than 400ppm, less than 300ppm, or less than 200ppm. There is no particular limitation on the lower limit of the carbon content. The carbon content may be more than 0ppm, more than 10ppm, more than 50ppm, more than 100ppm, or more than 150ppm. As described later, such a positive electrode active material with a small amount of carbon can be manufactured by heating (additional sintering) the oxide containing Li obtained after ion exchange.

[0032] The carbon content of the positive electrode active material can be measured, for example, by a combustion-infrared absorption method. As a measuring device, a carbon-sulfur analyzer (CS844 model) manufactured by LECO Corporation is used.

[0033] 1.4 Sulfur content

[0034] In addition to the above-mentioned carbon amount, the positive electrode active material involved in one embodiment may also have a sulfur amount of less than 300 ppm on a mass basis. By reducing the sulfur amount of the positive electrode active material, the resistance in the positive electrode active material is easily further reduced. There is no particular limitation on the lower limit of the sulfur amount. The sulfur amount may be greater than 0 ppm, greater than 10 ppm, greater than 50 ppm, greater than 100 ppm, greater than 150 ppm or greater than 200 ppm. As described later, such a positive electrode active material with a small amount of sulfur can be manufactured by washing the Li-containing oxide obtained after ion exchange.

[0035] The sulfur content of the positive electrode active material can be measured, for example, by combustion-ion chromatography. As measuring devices, a sample combustion device (AQF-2100S) manufactured by Mitsubishi Chemical Analytical Science Co., Ltd. and an ion chromatograph (Compact IC Flex) manufactured by Metrohm Japan Co., Ltd. are used.

[0036] 1.5 Carbon / Sulfur Ratio

[0037] The mass ratio C / S of carbon and sulfur in the positive electrode active material according to one embodiment may be, for example, 0.70 to 3.50, or 0.74 to 3.46. When the mass ratio of carbon to sulfur in the positive electrode active material is within such a range, it is easy to become a positive electrode active material with better performance balance.

[0038] 1.6 Shape

[0039] The positive electrode active material involved in one embodiment can be obtained by replacing Na of an oxide containing Na with a P2-type structure with Li. Among them, the P2-type structure is a hexagonal system, the diffusion coefficient of Na ions is large, and it is easy to crystallize and grow in a specific direction. In particular, when at least one of Mn, Ni and Co is included as a transition metal element constituting the P2-type structure, it is easy to crystallize and grow into a plate in a specific direction. Therefore, the oxide containing Na with a P2-type structure usually becomes a plate-like particle with a large aspect ratio in which the growth direction of the crystal is biased toward a specific direction. The positive electrode active material involved in one embodiment can be obtained based on such a plate-like oxide particle containing Na, or it can be obtained based on a spherical oxide particle containing Na as described later. That is, the shape of the positive electrode active material can be a plate-like particle or a spherical particle. In the case where the positive electrode active material is a spherical particle, due to the reduction in the size of the crystallite, the reaction resistance is reduced, and the diffusion resistance inside the particle is easily reduced. Furthermore, in the case of application to batteries, it is believed that by spheroidization, the curvature is reduced and the lithium ion conduction resistance is reduced. Thus, for example, the rate characteristics are improved and the reversible capacity is easily increased. It should be noted that in the present application, the so-called "spherical particles" refer to particles with a circularity of 0.80 or more. The circularity of the particles may be 0.81 or more, 0.82 or more, 0.83 or more, 0.84 or more, 0.85 or more, 0.86 or more, 0.87 or more, 0.88 or more, 0.89 or more, or 0.90 or more. The circularity of the particles is expressed by 4πS / L 2 Definition. Wherein, S is the orthographic projection area of ​​the particle, and L is the perimeter of the orthographic projection image of the particle. The circularity of the particle can be obtained by observing the appearance of the particle using a scanning electron microscope (SEM), a transmission electron microscope (TEM), or an optical microscope.

[0040] The positive electrode active material involved in one embodiment may be, for example, solid particles, hollow particles, or particles with voids. There is no particular limitation on the size of the positive electrode active material particles, and smaller sizes are considered advantageous. For example, the average particle size (D50) of the positive electrode active material particles may be greater than 0.1 μm and less than 10 μm, greater than 1.0 μm and less than 8.0 μm, or greater than 2.0 μm and less than 6.0 μm. It should be noted that the average particle size (D50) is the particle size (D50, median diameter) at the cumulative value of 50% in the volume-based particle size distribution obtained by laser diffraction and scattering method.

[0041] 2. Method for producing positive electrode active material

[0042] like Figure 1 As shown, a method for manufacturing a positive electrode active material according to an embodiment may include:

[0043] S1: exchanging at least a portion of Na in the Na-containing oxide having a P2-type structure with Li to obtain a Li-containing oxide having an O2-type structure; and

[0044] S2: heating the Li-containing oxide to reduce the carbon content of the Li-containing oxide.

[0045] 2.1S1

[0046] In S1, at least a part of Na in the Na-containing oxide having a P2 type structure is ion-exchanged with Li to obtain a Li-containing oxide having an O2 type structure.

[0047] 2.1.1 Preparation of Na-containing oxides with P2-type structure

[0048] The Na-containing oxide having a P2-type structure can be obtained, for example, by the following steps:

[0049] S1-1: obtaining a precursor (for example, a precursor containing at least one element of Mn, Ni and Co);

[0050] S1-2: coating the surface of the precursor with a Na source to obtain a composite; and

[0051] S1-3: sintering the composite.

[0052] In S1-1, for example, a precursor containing at least one element of Mn, Ni and Co is obtained. The precursor may contain at least Mn, and one or both selected from Ni and Co, and may contain at least Mn, Ni and Co. The precursor may be a salt containing at least one element of Mn, Ni and Co. For example, the precursor may be at least one of carbonate, sulfate, nitrate and acetate. Alternatively, the precursor may be a compound other than a salt. For example, the precursor may be a hydroxide. The precursor may be a hydrate. The precursor may be a combination of multiple compounds. The precursor may be in various shapes. For example, the precursor may be in the form of particles, or may be spherical particles as described later. There is no particular limitation on the particle size of the particles formed by the precursor. In S1-1, an ion source that can form a precipitate with transition metal ions in an aqueous solution and a transition metal compound containing at least one element of Mn, Ni and Co can be used, and a coprecipitation method can be used to obtain a precipitate as the above-mentioned precursor. Thus, spherical particles as a precursor can be easily obtained. "An ion source that can form a precipitate with transition metal ions in an aqueous solution" can be, for example, at least one selected from sodium salts such as sodium carbonate and sodium nitrate, sodium hydroxide, and sodium oxide. The transition metal compound can be the above-mentioned salt or hydroxide containing at least one element of Mn, Ni, and Co. Specifically, in S1-1, after the ion source and the transition metal compound are made into solutions respectively, each solution is dripped and mixed, so that a precipitate as a precursor can be obtained. At this time, as a solvent, for example, water is used. At this time, as a base, various sodium compounds can be used, and in addition, in order to adjust the alkalinity, an aqueous ammonia solution can be added. In the case of a co-precipitation method, for example, by preparing an aqueous solution of a transition metal compound and an aqueous solution of sodium carbonate, each aqueous solution is dripped and mixed, so as to obtain a precipitate as a precursor. Alternatively, the precursor can also be obtained by a sol-gel method. In particular, according to the co-precipitation method, spherical particles as a precursor are easily obtained. In S1-1, the precursor may contain element M. The element M is at least one selected from B, Mg, Al, K, Ca, Ti, V, Cr, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo and W. These elements M, for example, have the function of stabilizing the P2 type structure and the O2 type structure. The method for obtaining the precursor containing the element M is not particularly limited. In the case where the precursor is obtained by the coprecipitation method in S1-1, for example, an aqueous solution of a transition metal compound containing at least one of Mn, Ni and Co, an aqueous solution of sodium carbonate, and an aqueous solution of a compound of the element M are prepared, and each aqueous solution is dripped and mixed to obtain a precursor containing at least one element of Mn, Ni and Co while also containing the element M. Alternatively, in the manufacturing method disclosed in the present invention, the element M may not be added in S1-1, and the element M may be doped when the Na-doping sintering is performed in S1-2 and S1-3 described later.

[0053] In S1-2, the surface of the precursor obtained by S1-1 is coated with a Na source to obtain a composite. The Na source can be a salt containing Na such as carbonates and nitrates, or a compound other than salts such as sodium oxide and sodium hydroxide. In S1-2, the amount of the Na source coated on the surface of the precursor can be determined by adding the portion of Na that disappears during the subsequent calcination. In S1-2, the coverage rate of the Na source relative to the surface of the precursor is not particularly limited. For example, in S1-2, the above-mentioned composite can be obtained by coating more than 40 area%, more than 50 area%, more than 60 area% or more than 70 area% of the surface of the above-mentioned precursor with a Na source. Here, in the case where the precursor obtained by S1-1 is a spherical particle, and the composite obtained by S1-2 is obtained by coating more than 40 area% of the surface of the precursor with the Na source, in S1-3 described later, the oxide containing Na with a P2 type structure is easy to become a spherical particle. If the coverage of the Na source is small, when the composite is fired, P2 type crystals are easy to grow on the surface of the composite, and the oxide containing Na is easy to become plate-like. In the case where the coverage of the Na source is large, when the composite is fired, the crystallites of the P2 type crystals are easy to become smaller, and the oxide containing Na is easy to become spherical particles corresponding to the shape of the precursor. In S1-2, there is no particular limitation on the method of coating the surface of the above-mentioned precursor with a Na source. As mentioned above, in the case where more than 40% of the surface area of ​​the precursor is coated with a Na source, various methods can be listed as its method. For example, a tumbling flow coating method and a spray drying method can be listed. That is, a coating solution dissolved with a Na source is prepared, and the coating solution is dried while or after contacting the surface of the precursor. By adjusting the conditions of coating (temperature, time, number of times, etc.), more than 40% of the surface area of ​​the precursor can be coated with a Na source. In S1-2, for the precursor, an M source can also be coated together with a Na source. For example, in S1-2, the precursor obtained by S1-1, the Na source, and the M source containing at least one element M selected from B, Mg, Al, K, Ca, Ti, V, Cr, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo and W can be mixed to obtain a composite. The M source can be, for example, a salt containing the element M such as a carbonate or sulfate, or a compound other than a salt such as an oxide or hydroxide. The amount of the M source relative to the precursor can be determined according to the chemical composition of the oxide containing Na after sintering.

[0054] In S1-3, the composite obtained in S1-2 is calcined to obtain an oxide containing Na and having a P2 type structure. S1-3 includes, for example, the following S1-3A, S1-3B, and S1-3C.

[0055] In S1-3A, the composite is pre-fired at a temperature of 300°C to 700°C for 2 hours to 10 hours. In S1-3A, the pre-fired can be performed after the composite is arbitrarily formed. The pre-fired is performed at a temperature lower than that of the main calcination. If the pre-fired in S1-3A is insufficient, the formation of the P2 phase in the finally obtained Na-containing oxide may become insufficient. In S1-3A, by setting the pre-fired temperature to 300°C to 700°C and the pre-fired time to 2 hours to 10 hours, the composite can be sufficiently pre-fired, the thermal uniformity is improved, and the Na-containing oxide obtained by the later-described S1-3B and S1-3C is easy to become appropriate. The pre-firing temperature may be 400° C. to less than 700° C., 450° C. to less than 700° C., 500° C. to less than 700° C., 550° C. to less than 700° C., or 550° C. to 650° C. In addition, the pre-firing time may be 2 hours to 8 hours, 3 hours to 8 hours, 4 hours to 8 hours, 5 hours to 8 hours, or 5 hours to 7 hours. The pre-firing atmosphere is not particularly limited, and may be, for example, an oxygen-containing atmosphere.

[0056] In S1-3B, following the above-mentioned pre-calcination, the composite is subjected to main calcination for more than 30 minutes and less than 10 hours at a temperature of more than 700°C and less than 1100°C. In S1-3B, the main calcination temperature of the composite is more than 700°C and less than 1100°C, preferably more than 800°C and less than 1000°C. If the main calcination temperature is too low, the P2 phase is not generated, and if the main calcination temperature is too high, the O3 phase is easily generated instead of the P2 phase. There is no particular limitation on the temperature increase conditions from the pre-calcination temperature to the main calcination temperature. There is no particular limitation on the main calcination time, for example, it can be more than 30 minutes and less than 48 hours. However, the main calcination time can be used to control the shape of the oxide containing Na. As described above, in the method disclosed in the present invention, when the coverage of the Na source in the composite is 40 area% or more, when the composite is calcined, small microcrystalline P2-type crystals are easily formed on its surface. In the method disclosed in the present invention, a P2 type crystal is grown along the surface of the particle in a manner that a P2 type microcrystal is interconnected with another P2 type microcrystal, so that the shape of the oxide containing Na becomes a shape corresponding to the shape of the precursor. For example, when the precursor is a spherical particle, the oxide containing Na can also become a spherical particle. If the main firing time is too short, the generation of the P2 phase becomes insufficient. On the other hand, if the main firing time is too long, the P2 phase grows excessively and becomes a plate-like particle instead of a spherical one. According to the inventors, when the main firing time is more than 30 minutes and less than 3 hours, spherical particles of the oxide containing Na are easily obtained. The oxide containing Na obtained after the main firing has a plurality of microcrystals on the surface, and may have a structure in which the microcrystals are interconnected.

[0057] In S1-3C, following the above-mentioned main calcination, the composite is rapidly cooled (cooled at a temperature drop rate of 20°C / min or more) from a temperature T1 of more than 200°C to a temperature T2 of less than 100°C. The above-mentioned preliminary calcination and main calcination are performed, for example, in a heating furnace. In step S3-3, for example, after the main calcination of the composite is performed in a heating furnace, it is cooled to an arbitrary temperature T1 of more than 200°C in the heating furnace. After reaching the temperature T1, the calcined product is taken out of the heating furnace and rapidly cooled outside the furnace to an arbitrary temperature T2 of less than 100°C. Temperature T1 is an arbitrary temperature of more than 200°C, and can be an arbitrary temperature of more than 250°C. Temperature T2 is an arbitrary temperature of less than 100°C, and can be an arbitrary temperature of less than 50°C, and can be the cooling end temperature. In the specified temperature range from temperature T1 to temperature T2, moisture easily penetrates into the interlayers of the P2 type structure due to atomic vibration, molecular motion, etc. It is believed that by making the time of the temperature region where moisture is easily invaded short (i.e., rapid cooling) when cooling the composite body (Na-containing oxide having a P2-type structure) after the main firing, the amount of moisture intruding into the interlayers of the P2-type structure is reduced. In this regard, in step S3-3, when cooling the composite body after the main firing, from any temperature T1 above 200°C to any temperature T2 below 100°C, for example, cooling is performed using a dry atmosphere outside the furnace, so that the cooling rate from temperature T1 to temperature T2 becomes fast (e.g., 20°C / min or more), moisture is difficult to invade into the interlayers of the P2-type structure, and the collapse of the P2-type structure can be suppressed. As a result, Na can be efficiently ion-exchanged for Li in S4.

[0058] As described above, by using S1-1 to S1-3, it is possible to manufacture an oxide containing Na having a P2 type structure and a prescribed chemical composition. The oxide containing Na, for example, contains at least one transition metal element among Mn, Ni and Co, Na and O as constituent elements. Among them, when at least Na, Mn, and at least one selected from Ni and Co, and O are contained as constituent elements, in particular, when at least Na, Mn, Ni, Co, and O are contained as constituent elements, the performance of the positive electrode active material is likely to be further improved. The oxide containing Na may have a composition consisting of Na c Mn x-p Ni y-q Co z-r M p+q+rThe chemical composition represented by O2. Wherein, 0<c<1.00, x+y+z=1, and 0≤p+q+r<0.17. In addition, M is an element selected from at least one of B, Mg, Al, K, Ca, Ti, V, Cr, Fe, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo and W. In the case where the oxide containing Na has such a chemical composition, it is easy to further maintain the P2 type structure. In the above chemical composition, c is greater than 0, and can be greater than 0.10, greater than 0.20, greater than 0.30, greater than 0.40, greater than 0.50 or greater than 0.60, and is less than 1.00, and can be less than 0.90, less than 0.80 or less than 0.70. x is 0 or more, and may be 0.10 or more, 0.20 or more, 0.30 or more, or 0.40 or more, and is 1.00 or less, and may be 0.90 or less, 0.80 or less, 0.70 or less, 0.60 or less, 0.50 or less, or 0.40 or less. In addition, y is 0 or more, and may be 0.10 or more, or 0.20 or more, and is 1.00 or less, and may be 0.90 or less, 0.80 or less, 0.70 or less, 0.60 or less, 0.50 or less, 0.40 or less, 0.30 or less, or 0.20 or less. In addition, z is 0 or more, and may be 0.10 or more, 0.20 or more, 0.30 or more, or 0.40 or more, and is 1.00 or less, and may be 0.90 or less, 0.80 or less, 0.70 or less, 0.60 or less, 0.50 or less, or 0.40 or less. Element M contributes less to charge and discharge. In this regard, in the above-mentioned chemical composition, by p+q+r being less than 0.17, it is easy to ensure a high charge and discharge capacity. p+q+r may be less than 0.16, less than 0.15, less than 0.14, less than 0.13, less than 0.12, less than 0.11 or less than 0.10. On the other hand, by including the element M, the P2 type structure and the O2 type structure are easily stabilized. In the above-mentioned chemical composition, p+q+r is greater than 0, and may be greater than 0.01, greater than 0.02, greater than 0.03, greater than 0.04, greater than 0.05, greater than 0.06, greater than 0.07, greater than 0.08, greater than 0.09 or greater than 0.10. The composition of O is approximately 2, but is not limited to exactly 2.0 and is variable.

[0059] 2.1.2 Ion exchange

[0060] In S1, an oxide containing Li having an O2 type structure is obtained by ion-exchanging at least a portion of Na in the oxide containing Na obtained as described above with Li. Regarding ion exchange, there are, for example, a method using an aqueous solution containing lithium halides and a method using a mixture of lithium halides and other lithium salts (e.g., a molten salt). From the viewpoint that the P2 type structure is easily destroyed by the intrusion of water and the viewpoint of crystallinity, the method using a molten salt is preferred in the above two methods. That is, by mixing the above-mentioned oxide containing Na with the P2 type structure with the molten salt and heating it to a temperature above the melting point of the molten salt, at least a portion of Na in the oxide containing Na can be replaced with Li by ion exchange. The lithium halide constituting the molten salt is preferably at least one of lithium chloride, lithium bromide and lithium iodide. The other lithium salts constituting the molten salt are preferably lithium nitrate. By using a molten salt, the melting point is reduced compared to the case where a lithium halide or other lithium salt is used alone, and ion exchange at a lower temperature can be performed. The temperature in the ion exchange may be, for example, above the melting point of the above-mentioned molten salt, and below 600° C., below 500° C., below 400° C., or below 300° C. If the temperature in the ion exchange is too high, an O3 type structure as a stable phase is easily generated instead of an O2 type structure. On the other hand, from the viewpoint of shortening the time required for ion exchange, the temperature in the ion exchange is preferably as high as possible.

[0061] 2.2S2

[0062] In S2, the Li-containing oxide obtained in S1 is heated to reduce the carbon content of the Li-containing oxide. That is, by additionally calcining the Li-containing oxide having an O2 type structure obtained after ion exchange, at least a portion of the carbon (lithium carbonate) present on the surface of the Li-containing oxide is removed.

[0063] The Li-containing oxide having an O2-type structure adopts a Li-deficient crystal structure. That is, the composition ratio of Li to O in the positive electrode active material having an O2-type structure is less than 0.5 (for example, "a" in the above composition formula is less than 1.0), and there is room for Li to be inserted into the crystal structure. When such a Li-deficient Li-containing oxide is heated, Figure 2 As shown in FIG. 1 , it is believed that the lithium carbonate on the surface of the Li-containing oxide is decomposed into Li and CO x , Li enters the crystal structure, on the other hand, CO xRemoved outside the oxide containing Li. That is, by performing additional calcination on the oxide containing Li having an O2 type structure obtained after ion exchange, at least a portion of the carbon (lithium carbonate) present on the surface of the oxide containing Li is removed, and the carbon content of the finally obtained positive electrode active material becomes less than 500 ppm. Such an action and effect is unique to heating the oxide containing Li having an O2 type structure.

[0064] In S2, the atmosphere when the oxide containing Li is heated can be any atmosphere that maintains the O2 type structure of the oxide containing Li and can reduce the amount of carbon in the oxide containing Li. For example, the heating atmosphere can be an inert gas atmosphere such as Ar atmosphere, or an oxygen-containing atmosphere such as air atmosphere.

[0065] In S2, the temperature at which the oxide containing Li is heated can be any temperature that maintains the O2 type structure of the oxide containing Li and can reduce the amount of carbon in the oxide containing Li. If the temperature is too low, the above-mentioned carbon removal reaction is difficult to occur. On the other hand, if the temperature is too high, the O2 type structure as a quasi-stable phase is easily changed to an O3 type structure as a stable phase. From the viewpoint of maintaining the O2 type structure while appropriately removing carbon, the temperature in S2 can be, for example, above 200°C and below 300°C. The temperature can be above 220°C or above 240°C, and can be below 280°C or below 260°C.

[0066] In S2, the time for heating the oxide containing Li is sufficient as long as the O2 type structure of the oxide containing Li is maintained and the amount of carbon in the oxide containing Li can be reduced. The time in S2 (the holding time at the above-mentioned heating temperature) can be, for example, 30 minutes to 10 hours, 2 hours to 8 hours, or 4 hours to 6 hours.

[0067] 2.3 Other processes

[0068] According to the method including the above S1 and S2, a positive electrode active material having an O2 type structure and a carbon content of less than 500ppm can be manufactured. Furthermore, a method for manufacturing a positive electrode active material according to an embodiment may include: washing the Li-containing oxide obtained by S1 with water to reduce the sulfur content of the Li-containing oxide. The washing of the Li-containing oxide may be performed before the above-mentioned S2 or after the above-mentioned S2. In particular, it is believed that by washing with water before the above-mentioned S2 and then performing S2, it is also possible to reduce the amount of water while reducing the carbon and sulfur content in the positive electrode active material. By washing the Li-containing oxide with water, the sulfur content of the finally obtained positive electrode active material becomes less than 300ppm. It should be noted that washing the Li-containing oxide with water is effective in reducing the sulfur content of the finally obtained positive electrode active material, but is basically ineffective in reducing the carbon content. In order to reduce the carbon content of the finally obtained positive electrode active material, for example, the above-mentioned additional calcination is necessary.

[0069] 3. Lithium-ion battery

[0070] Figure 3 The structure of a lithium ion battery according to one embodiment is schematically shown in FIG. Figure 3 As shown, a lithium ion battery 100 according to one embodiment includes a positive electrode active material layer 10, an electrolyte layer 20, and a negative electrode active material layer 30. The positive electrode active material layer 10 includes the positive electrode active material according to the above embodiment. Figure 3 As shown, the lithium-ion battery 100 may include a positive electrode current collector 40 and a negative electrode current collector 50 .

[0071] 3.1 Positive electrode active material layer

[0072] The positive electrode active material layer 10 contains the positive electrode active material having the O2 type structure described above. The positive electrode active material layer 10 may optionally contain other positive electrode active materials, electrolytes, conductive aids, binders, etc. In addition, the positive electrode active material layer 10 may contain various additives. The respective contents of the positive electrode active material, electrolyte, conductive aid, binder, etc. in the positive electrode active material layer 10 may be appropriately determined according to the target battery performance. For example, when the solid content contained in the positive electrode active material layer 10 is set to 100% by mass as a whole, the content of the positive electrode active material may be greater than 40% by mass and less than 100% by mass.

[0073] An ion-conductive protective layer may be formed on the surface of the positive electrode active material. That is, the positive electrode active material layer 10 may include a composite of the positive electrode active material and the protective layer, in which at least a portion of the surface of the positive electrode active material may be covered with the protective layer. The ion-conductive protective layer may include various ion-conductive compounds. The ion-conductive compound may be, for example, at least one selected from ion-conductive oxides and ion-conductive halides. The coverage rate (area rate) of the protective layer relative to the surface of the positive electrode active material may be, for example, greater than 70%, greater than 80%, or greater than 90%. The thickness of the protective layer may be, for example, greater than 0.1 nm or greater than 1 nm, and may be less than 100 nm or less than 20 nm.

[0074] The positive electrode active material contained in the positive electrode active material layer 10 may only include the above-mentioned positive electrode active material with O2 type structure, or may include the positive electrode active material and other positive electrode active materials (other positive electrode active materials) while including the positive electrode active material. From the viewpoint of further improving the effect produced by the technology disclosed in the present invention, the proportion of other positive electrode active materials in the positive electrode active material as a whole may be a small amount. For example, when the whole of the positive electrode active material is set to 100% by mass, the content of the above-mentioned positive electrode active material with O2 type structure may be 50% by mass or more and 100% by mass or less, 60% by mass or more and 100% by mass or less, 70% by mass or more and 100% by mass or less, 80% by mass or more and 100% by mass or less, 90% by mass or more and 100% by mass or less, 95% by mass or more and 100% by mass or less, or 99% by mass or more and 100% by mass or less.

[0075] The electrolyte that may be included in the positive electrode active material layer 10 may be a solid electrolyte, a liquid electrolyte, or a combination thereof. Among them, when the positive electrode active material layer 10 includes a solid electrolyte, especially when it includes a sulfide solid electrolyte, it is easy to ensure high performance. The sulfide solid electrolyte may be a glass-based sulfide solid electrolyte (sulfide glass), a glass-ceramic sulfide solid electrolyte, or a crystalline sulfide solid electrolyte. Sulfide glass is amorphous. Sulfide glass may have a glass transition temperature (Tg). In addition, when the sulfide solid electrolyte has a crystalline phase, as the crystalline phase, for example, Thio-LISICON type crystal phase, LGPS type crystal phase, and silver-germanite type crystal phase can be listed. The sulfide solid electrolyte may contain, for example, Li element, P element, and S element. The sulfide solid electrolyte may further contain X element (X is at least one of As, Sb, Si, Ge, Sn, B, Al, Ga, and In). In addition, the sulfide solid electrolyte may further contain at least one of O element and halogen element. In addition, the sulfide solid electrolyte may contain S element as the main component of the anion element. For example, the sulfide solid electrolyte may be selected from Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-GeS2, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-P2S5-LiI-LiBr, Li2S-SiS2-P2S5-LiI, Li2S-P2S5-ZmSn (where m and n are positive numbers. Z is any one of Ge, Zn, and Ga.), Li2S-SiS2-Li3PO4, Li2S-SiS2-Li x MO y (wherein x and y are positive numbers. M is at least one of P and any one of Si, Ge, B, Al, Ga, and In.) Alternatively, the sulfide solid electrolyte is not particularly limited, and for example, it may have a chemical composition selected from at least one of xLi2S·(100-x)P2S5(70≤x≤80), yLiI·zLiBr·(100-yz)(xLi2S·(1-x)P2S5)(0.7≤x≤0.8, 0≤y≤30, 0≤z≤30), etc. Alternatively, the sulfide solid electrolyte may have a general formula: Li 4-x Ge 1-x P xThe chemical composition represented by S4 (0<x<1). In the above general formula, at least a part of Ge can be replaced by at least one of Sb, Si, Sn, B, Al, Ga, In, Ti, Zr, V and Nb. In the above general formula, a part of P can be replaced by at least one of Sb, Si, Sn, B, Al, Ga, In, Ti, Zr, V and Nb. In the above general formula, a part of Li can be replaced by at least one of Na, K, Mg, Ca and Zn. In the above general formula, a part of S can be replaced by halogen (at least one of F, Cl, Br and I). Alternatively, the sulfide solid electrolyte may have a Li 7-a PS 6-a X a (X is at least one of Cl, Br and I, and a is a number greater than 0 and less than 2). a may be 0 or greater than 0. In the latter case, a may be greater than 0.1, greater than 0.5, or greater than 1. In addition, a may be less than 1.8 or less than 1.5. The sulfide solid electrolyte may be in a particle form. The average particle size (D50) of the sulfide solid electrolyte may be, for example, greater than 10 nm and less than 100 μm.

[0076] As the conductive aid that can be contained in the positive electrode active material layer 10, for example, carbon materials such as vapor grown carbon fiber (VGCF), acetylene black (AB), Ketjen black (KB), carbon nanotubes (CNT), and carbon nanofibers (CNF); and metal materials such as nickel, titanium, aluminum, and stainless steel can be listed. The conductive aid can be, for example, in the form of particles or fibers, and there is no particular limitation on the size. The conductive aid can be used alone or in combination of two or more.

[0077] As the binder that can be contained in the positive electrode active material layer 10, for example, butadiene rubber (BR)-based binders, butylene rubber (IIR)-based binders, acrylate butadiene rubber (ABR)-based binders, styrene butadiene rubber (SBR)-based binders, polyvinylidene fluoride (PVdF)-based binders, polytetrafluoroethylene (PTFE)-based binders, polyimide (PI)-based binders, etc. can be listed. Only one type of binder can be used alone, or two or more types can be used in combination.

[0078] The positive electrode active material layer 10 may contain various additives, such as a dispersant and a lubricant, in addition to the above-mentioned components.

[0079] 3.2 Electrolyte layer

[0080] The electrolyte layer 20 is arranged between the positive electrode active material layer 10 and the negative electrode active material layer 30. The electrolyte layer 20 contains at least an electrolyte. The electrolyte layer 20 may contain at least one of a solid electrolyte and a liquid electrolyte, and may further optionally contain a binder, etc. Among them, when the electrolyte layer 20 contains a solid electrolyte, especially when it contains a sulfide solid electrolyte, it is easy to ensure higher performance. There is no particular limitation on the content of the electrolyte and the binder in the electrolyte layer 20. Alternatively, the electrolyte layer 20 may have a separator (diaphragm) for preventing the positive electrode active material layer 10 from contacting the negative electrode active material layer 30 while maintaining the electrolyte. There is no particular limitation on the thickness of the electrolyte layer 20, for example, it may be 0.1 μm or more or 1 μm or more, and may be 2 mm or less or 1 mm or less.

[0081] The electrolyte contained in the electrolyte layer 20 can be appropriately selected from the electrolytes (solid electrolytes and / or liquid electrolytes) exemplified as the electrolytes that can be contained in the above-mentioned positive electrode active material layer 10. In addition, for the binder that can be contained in the electrolyte layer 20, it can be appropriately selected from the binders exemplified as the binders that can be contained in the above-mentioned positive electrode active material layer. Electrolytes and binders can be used alone or in combination of two or more. The separator can be any separator commonly used in lithium-ion batteries, for example, separators composed of resins such as polyethylene (PE), polypropylene (PP), polyester and polyamide. The separator can be a single-layer structure or a multi-layer structure. As a separator of a multi-layer structure, for example, a separator of a two-layer structure of PE / PP, or a separator of a three-layer structure of PP / PE / PP or PE / PP / PE, etc. can be listed. The separator can be composed of non-woven fabrics such as cellulose non-woven fabrics, resin non-woven fabrics, and glass fiber non-woven fabrics.

[0082] 3.3 Negative electrode active material layer

[0083] The negative electrode active material layer 30 contains at least a negative electrode active material. In addition, the negative electrode active material layer 30 may optionally contain an electrolyte, a conductive aid, a binder, and various additives. The content of each component in the negative electrode active material layer 30 can be appropriately determined according to the target battery performance. For example, when the solid content of the negative electrode active material layer 30 is set to 100% by mass, the content of the negative electrode active material may be 40% by mass or more, 50% by mass or more, 60% by mass or more, or 70% by mass or more, and may be 100% by mass or less, less than 100% by mass, 95% by mass or less, or 90% by mass or less. Alternatively, when the negative electrode active material layer 30 is set to 100% by volume, the total amount of the negative electrode active material and the optional electrolyte, conductive aid, and binder may be 85% by volume or more, 90% by volume or more, or 95% by volume or more, and the remainder may be voids or other components. The shape of the negative electrode active material layer 30 is not particularly limited, and may be, for example, a sheet having a substantially flat surface. The thickness of the negative electrode active material layer 30 is not particularly limited, and may be, for example, 0.1 μm or more, 1 μm or more, 10 μm or more, or 30 μm or less, or 2 mm or less, 1 mm or less, 500 μm or less, or 100 μm or less.

[0084] As for the negative electrode active material contained in the negative electrode active material layer 30, any negative electrode active material known as a negative electrode active material for a lithium ion battery can be used. Among the known active materials, various materials whose potential for absorbing and releasing lithium ions (charge and discharge potential) is lower than that of the above-mentioned positive electrode active material can be used. For example, silicon-based active materials such as Si, Si alloys, and silicon oxide; carbon-based active materials such as graphite and hard carbon; various oxide-based active materials such as lithium titanate; metallic lithium, lithium alloys, etc. can be used. Among them, when the negative electrode active material layer 30 contains Si as a negative electrode active material, the performance of the lithium ion battery 100 is easily improved. The negative electrode active material can be used alone or in combination of two or more. The shape of the negative electrode active material can be a general shape of a negative electrode active material for a lithium ion battery. For example, the negative electrode active material can be in the form of particles. The negative electrode active material particles can be primary particles or secondary particles formed by the aggregation of multiple primary particles. The average particle size (D50) of the negative electrode active material particles may be, for example, 1 nm or more, 5 nm or more, or 10 nm or more, and may be 500 μm or less, 100 μm or less, 50 μm or less, or 30 μm or less. Alternatively, the negative electrode active material may be in the form of a sheet (foil, film) such as lithium foil. That is, the negative electrode active material layer 30 may be composed of a sheet of the negative electrode active material.

[0085] As the electrolyte that can be contained in the negative electrode active material layer 30, for example, the above-mentioned solid electrolyte, electrolyte solution, or a combination thereof can be cited. The conductive aid that can be contained in the negative electrode active material layer 30 can be appropriately selected from the conductive aids exemplified as the conductive aids that can be contained in the above-mentioned positive electrode active material layer. The binder that can be contained in the negative electrode active material layer 30 can be appropriately selected from the binders exemplified as the binders that can be contained in the above-mentioned positive electrode active material layer. The electrolyte, the conductive aid, and the binder can be used alone or in combination of two or more.

[0086] 3.4 Other components

[0087] like Figure 3 As shown, the lithium-ion battery 100 may include a positive electrode collector 40 in contact with the positive electrode active material layer 10 and a negative electrode collector 50 in contact with the negative electrode active material layer 30. The structure of the collector itself is well known. In addition to the above-mentioned structure, the lithium-ion battery 100 may include a general structure as a battery. For example, a pole piece, a terminal, etc. As for the lithium-ion battery 100, the above-mentioned structures can be accommodated inside the outer packaging body. As for the outer packaging body, any outer packaging body known as the outer packaging body of the battery can be used. In addition, multiple batteries 100 can be electrically connected arbitrarily, or overlapped arbitrarily to form a battery group. In this case, the battery group can be accommodated inside a known battery casing. As the shape of the lithium-ion battery 100, for example, a coin type, a stacked body type, a cylindrical type, and a square type can be listed. The lithium-ion battery 100 can be a secondary battery.

[0088] The lithium ion battery 100 can be manufactured by applying a known method except for using the above-mentioned specific positive electrode active material. For example, it can be manufactured as follows.

[0089] (1) The positive electrode active material constituting the positive electrode active material layer is dispersed in a solvent to obtain a positive electrode layer slurry. The solvent used in this case is not particularly limited, and water or various organic solvents can be used. The positive electrode layer slurry is applied to the surface of the positive electrode collector using a scraper or the like, and then dried to form a positive electrode active material layer on the surface of the positive electrode collector to prepare a positive electrode.

[0090] (2) The negative electrode active material constituting the negative electrode active material layer is dispersed in a solvent to obtain a negative electrode layer slurry. The solvent used in this case is not particularly limited, and water or various organic solvents can be used. The negative electrode layer slurry is applied to the surface of the negative electrode collector using a scraper or the like, and then dried to form a negative electrode active material layer on the surface of the negative electrode collector to prepare a negative electrode.

[0091] (3) The layers are stacked in a manner such that the electrolyte layer (solid electrolyte layer or separator) is sandwiched between the negative electrode and the positive electrode to obtain a stack having a negative electrode collector, a negative electrode active material layer, an electrolyte layer, a positive electrode active material layer and a positive electrode collector in this order. Other components such as terminals are installed on the stack as needed.

[0092] (4) The stacked body is housed in a battery case, and in the case of an electrolyte battery, the battery case is filled with an electrolyte, the stacked body is immersed in the electrolyte, and the stacked body is sealed in the battery case to complete the battery. In the case of an electrolyte battery, in the above-mentioned stage (3), the negative electrode active material layer, the separator, and the positive electrode active material layer may contain an electrolyte.

[0093] The technology of the present disclosure will be described in more detail below with reference to examples, but the technology of the present disclosure is not limited to the following examples.

[0094] 1. Preparation of positive electrode active material

[0095] 1.1 Example 1

[0096] 1.1.1 Preparation of precursor particles

[0097] (1) MnSO4·5H2O, NiSO4·6H2O, and CoSO4·7H2O were weighed to obtain a target composition ratio and dissolved in distilled water to a concentration of 1.2 mol / L to obtain a first solution. In addition, Na2CO3 was dissolved in distilled water in another container to a concentration of 1.2 mol / L to obtain a second solution.

[0098] (2) 1000 mL of pure water was placed in a reaction container (with a baffle), and 500 mL of the first solution and 500 mL of the second solution were added dropwise at a rate of about 4 mL / min.

[0099] (3) After the dropwise addition was completed, the mixture was stirred at room temperature at a stirring speed of 100 rpm for 1 hour to obtain a product.

[0100] (4) The product is washed with pure water, separated into solid and liquid using a centrifuge, and the precipitate is recovered.

[0101] (5) The obtained precipitate was dried at 120°C overnight, crushed in a mortar, and then separated into coarse particles and fine particles by air flow classification. The coarse particles and fine particles are both composite salts containing Mn, Ni, and Co. In Example 1, the above-mentioned coarse particles were used as precursor particles.

[0102] 1.1.2 Preparation of composite particles

[0103] (1) Na 2 CO 3 and distilled water were weighed to give 1150 g / L, and then stirred with a stirrer until the mixture was completely dissolved to prepare a Na 2 CO 3 aqueous solution.

[0104] (2) The above-mentioned precursor particles are mixed in a Na2CO3 aqueous solution to prepare a slurry. Na2CO3 and the above-mentioned precursor particles are mixed to form a target composition after sintering as described below. 0.7 Mn 0.4 Ni 0.2 Co 0.4 O2 way mix.

[0105] (3) Dry the obtained slurry by spray drying. Specifically, a spray drying device DL410 was used at a slurry feeding rate of 30 mL / min, an inlet temperature of 200°C, and a circulating air volume of 0.8 m 3 Under the conditions of 0.504 wt % / min and a spray pressure of 0.3 MPa, 70% or more of the surface of the above-mentioned precursor particles was coated with Na2CO3 to obtain composite particles.

[0106] 1.1.3 Calcination of composite particles

[0107] The composite particles were placed in an alumina crucible and fired in an air atmosphere to obtain an oxide containing Na and having a P2 type structure. The firing conditions were as described in the following (1) to (7).

[0108] (1) An alumina crucible containing the composite particles is placed in a heating furnace in an air atmosphere.

[0109] (2) The temperature in the heating furnace was raised from room temperature (25°C) to 600°C over 115 minutes.

[0110] (3) The temperature in the heating furnace is maintained at 600° C. for 360 minutes for preliminary calcination.

[0111] (4) After the pre-sintering, the temperature in the heating furnace was raised from 600°C to 800°C over 60 minutes.

[0112] (5) Maintain the temperature in the heating furnace at 800°C for 60 minutes to perform main sintering.

[0113] (6) After the main firing, the temperature in the heating furnace was lowered from 800°C to 250°C over 80 minutes.

[0114] (7) The alumina crucible was taken out from the heating furnace at 250°C and allowed to cool in a dry atmosphere.

[0115] The calcined product after cooling was pulverized using a mortar in a dry atmosphere to obtain Na-containing oxide particles having a P2 type structure.

[0116] 1.1.4 Ion exchange

[0117] (1) LiNO 3 and LiCl were weighed to a molar ratio of 50:50, and mixed with the above-mentioned Na-containing oxide particles at a molar ratio of 10 times the minimum amount of Li required for ion exchange to obtain a mixture.

[0118] (2) Using an alumina crucible, ion exchange was performed in an air atmosphere at 280° C. for 1 hour to obtain a product including oxide particles containing Li.

[0119] (3) The salt remaining in the product was washed with pure water, and solid-liquid separation was performed by vacuum filtration to obtain a precipitate.

[0120] (4) The obtained precipitate was dried at 120° C. overnight to obtain Li-containing oxide particles having an O2 type structure.

[0121] 1.1.5 Additional sintering

[0122] The obtained Li-containing oxide particles were placed in an alumina crucible and sintered at 250° C. for 5 hours in an Ar atmosphere to obtain the positive electrode active material of Example 1. XRD confirmed that the positive electrode active material of Example 1 had an O2 type structure.

[0123] 1.2 Example 2

[0124] 1.2.1 Preparation of precursor particles

[0125] In the same manner as in Example 1, precursor particles were produced.

[0126] 1.2.2 Preparation of composite particles

[0127] The target composition after firing is Na 0.7 Mn 0.5 Ni 0.2 Co 0.3 Composite particles were prepared in the same manner as in Example 1, except that Na 2 CO 3 and the above-mentioned precursor particles were mixed in the form of O 2 to obtain a slurry.

[0128] 1.2.3 Calcination of composite particles

[0129] The composite particles were placed in an alumina crucible and fired in an air atmosphere to obtain an oxide containing Na and having a P2 type structure. The firing conditions were as described in the following (1) to (7).

[0130] (1) An alumina crucible containing the composite particles is placed in a heating furnace in an air atmosphere.

[0131] (2) The temperature in the heating furnace was raised from room temperature (25°C) to 600°C over 115 minutes.

[0132] (3) The temperature in the heating furnace is maintained at 600° C. for 360 minutes for preliminary calcination.

[0133] (4) After the pre-sintering, the temperature in the heating furnace was raised from 600°C to 900°C over 100 minutes.

[0134] (5) Maintain the temperature in the heating furnace at 900°C for 60 minutes to perform main sintering.

[0135] (6) After the main firing, the temperature in the heating furnace was lowered from 900°C to 250°C over 120 minutes.

[0136] (7) The alumina crucible was taken out from the heating furnace at 250°C and allowed to cool in a dry atmosphere.

[0137] 1.2.4 Ion exchange and additional calcination

[0138] In the same manner as in Example 1, ion exchange and additional calcination were performed after mortar pulverization to obtain the positive electrode active material according to Example 2. XRD confirmed that the positive electrode active material according to Example 2 had an O2 type structure.

[0139] 1.3 Example 3

[0140] The steps until ion exchange were the same as those in Example 2. The Li-containing oxide particles obtained after ion exchange were placed in an alumina crucible and sintered at 250° C. for 5 hours in an atmospheric atmosphere (air atmosphere) to obtain the positive electrode active material involved in Example 3. XRD was used to confirm that the positive electrode active material involved in Example 3 had an O2 type structure.

[0141] 1.4 Comparative Example 1

[0142] Except that the additional calcination was not performed, the same procedures were followed as in Examples 2 and 3. XRD confirmed that the positive electrode active material of Comparative Example 1 had an O2 type structure.

[0143] 1.5 Comparative Examples 2 and 3

[0144] As a Li non-deficient positive electrode active material, a positive electrode active material having an O3 type structure was prepared. The positive electrode active material involved in Comparative Example 2 is an NCA-based positive electrode active material (LiNi 0.85 Co 0.10 Al 0.05 O2), the positive electrode active material involved in Comparative Example 3 is an NCM-based positive electrode active material (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3O2). The positive electrode active materials involved in Comparative Examples 2 and 3 are both obtained by mixing a Li source and a transition metal source and calcining them at a high temperature.

[0145] 2. Quantification of impurities contained in positive electrode active materials

[0146] For each of the positive electrode active materials of Examples 1 to 3 and Comparative Examples 1 to 3, the carbon content, sulfur content, chlorine content, and nitrogen content were quantitatively determined by the following method.

[0147] (1) The carbon content in the sample was measured by the combustion-infrared absorption method. As a measuring device, a carbon-sulfur analyzer (CS844 model) manufactured by LECO Corporation was used.

[0148] (2) The sulfur and chlorine contents in the samples were measured by combustion-ion chromatography. As measuring devices, a sample combustion device (AQF-2100S) manufactured by Mitsubishi Chemical Analytical Science Co., Ltd. and an ion chromatograph (Compact IC Flex) manufactured by Metrohm Japan Co., Ltd. were used.

[0149] (3) The amount of nitrogen in the sample was measured by the inert gas fusion method. As a measuring device, EMGA-920-Ar manufactured by Horiba, Ltd. was used.

[0150] 3. Evaluation of battery cell production

[0151] Using each of the above-mentioned positive electrode active materials, a battery cell for evaluation was produced. The procedure for producing the battery cell for evaluation is as follows.

[0152] (1) The positive electrode active material, sulfide solid electrolyte (Li2S-P2S5-LiI-LiBr), PVDF, and VGCF were weighed and mixed so as to obtain a positive electrode composite material: sulfide solid electrolyte: PVDF: VGCF = 81.1:15.9:0.6:2.4 (mass ratio). The obtained positive electrode composite material was dispersed in a solvent (butyl butyrate) to obtain a positive electrode slurry. The obtained positive electrode slurry was applied to a positive electrode collector (Al foil) and dried. Then, a roller press was used to press at a linear pressure of 100 kN at the pressing temperature shown in Table 1 below to form a positive electrode active material layer on the surface of the positive electrode collector.

[0153] (2) Weigh and mix the negative electrode active material (lithium titanate), sulfide solid electrolyte (Li2S-P2S5-LiI-LiBr), PVDF and VGCF so that the negative electrode active material: sulfide solid electrolyte: PVDF: VGCF = 72.1: 22.7: 3.5: 1.7 (mass ratio), thereby obtaining a negative electrode composite. The obtained negative electrode composite is dispersed in a solvent (butyl butyrate) to obtain a negative electrode slurry. The obtained negative electrode slurry is applied to a negative electrode collector (Cu foil) and dried. Then, a roller press is used to press at a linear pressure of 60 kN at room temperature (25°C) to form a negative electrode active material layer on the surface of the negative electrode collector.

[0154] (3) A sulfide solid electrolyte (Li2S-P2S5-LiI-LiBr) and acrylate butadiene rubber (ABR) were weighed and mixed so as to become sulfide solid electrolyte:ABR=99.4:0.6 (mass ratio), thereby obtaining an electrolyte composite material.

[0155] (4) An electrolyte composite is sandwiched between the positive electrode active material layer and the negative electrode active material layer to obtain a laminate having a positive electrode collector, a positive electrode active material layer, a solid electrolyte layer, a negative electrode active material layer and a negative electrode collector in sequence. The obtained laminate is pressed to obtain an evaluation battery cell (solid battery).

[0156] 4. Evaluation of charge and discharge characteristics

[0157] For each evaluation battery cell of Examples 1 to 3 and Comparative Example 1, a charge and discharge test was performed for 2 cycles at 0.1C (1C = 220mA / g) in a constant temperature chamber maintained at 25°C in a voltage range of 1.8-4.6V. Then, in a constant temperature chamber maintained at 25°C, a current equivalent to 3C was applied for 10 seconds at SOC50% (2.35V vs. LTO), thereby measuring the DCIR resistance. The measurement results are shown in Table 1 below.

[0158] 5. Evaluation results

[0159] In the following Table 1, the crystal structure and chemical composition of the positive electrode active material, the atmosphere of the additional firing after ion exchange, the amount of impurities contained in the positive electrode active material (carbon amount, sulfur amount, chlorine amount, nitrogen amount), the identification results of the impurities using XPS, the position of the (002) plane peak using XRD, and the resistance measurement results of the evaluated battery cells are shown for Examples 1 to 3 and Comparative Examples 1 to 3, respectively.

[0160]

Table 1

[0161]

[0162] As shown in Table 1, the carbon content of the positive electrode active material in Comparative Example 1 is as high as 900 ppm, and as a result, the resistance of the evaluated battery cell becomes larger. The carbon content of the positive electrode active material in Examples 1 to 3 is as low as 500 ppm or less, and as a result, the resistance of the evaluated battery cell becomes smaller. It is believed that the positive electrode active material in Examples 1 to 3 is subjected to additional calcination of the Li-containing oxide after ion exchange, thereby decomposing part of the lithium carbonate as an impurity, and as a result, the carbon content is reduced ( Figure 2 ). Comparing Comparative Example 1 with Examples 1 to 3, the peak top of the 002 plane in the X-ray diffraction pattern migrates. This is believed to be because the lithium generated by the decomposition of lithium carbonate as an impurity is taken into the O2 type structure, and the c-axis length changes. Such decomposition and removal of impurities brought about by additional calcination is unique to the positive electrode active material having an O2 type structure as a Li-deficient structure.

[0163] Furthermore, the positive electrode active material involved in Comparative Example 2 has a large amount of carbon and sulfur. In addition, the positive electrode active material involved in Comparative Example 3 has a small amount of carbon but a large amount of sulfur. The positive electrode active materials involved in Comparative Examples 2 and 3 have a Li non-deficient O3 type structure, and it is believed that it is difficult to reduce the carbon content even if additional calcination is performed.

[0164] 6. Supplement

[0165] Furthermore, in the above-mentioned embodiments, the case of obtaining precursor particles by a coprecipitation method is illustrated, but the precursor particles can also be obtained by methods other than this. In addition, in the above-mentioned embodiments, the case of mixing the precursor particles and the Na2CO3 solution to obtain composite particles is illustrated, but the composite particles can also be obtained by methods other than this. In addition, in the above-mentioned embodiments, as the oxide containing Na with a P2 type structure and the oxide containing Li with an O2 type structure, substances with a prescribed chemical composition are illustrated, but the chemical composition of the oxide containing Na and the oxide containing Li is not limited thereto. For example, with respect to the oxide containing Na and the oxide containing Li, an element M other than Mn, Ni and Co can be doped. Regarding the element M, as described in the embodiment.

Claims

1. A positive electrode active material having an O2 type structure and having a carbon content of 500 ppm or less. 2 . The positive electrode active material according to claim 1 , which has a sulfur content of 300 ppm or less. 3 . A lithium ion battery comprising a positive electrode active material layer, an electrolyte layer and a negative electrode active material layer, wherein the positive electrode active material layer comprises the positive electrode active material according to claim 1 .

4. A method for producing a positive electrode active material, comprising: ion-exchanging at least a portion of Na in the Na-containing oxide having a P2-type structure with Li to obtain a Li-containing oxide having an O2-type structure; and The Li-containing oxide is heated to reduce the carbon content of the Li-containing oxide.

5. The method for producing a positive electrode active material according to claim 4, wherein: The atmosphere when the Li-containing oxide is heated is an inert gas atmosphere or an oxygen-containing atmosphere, and the temperature when the Li-containing oxide is heated is 200° C. or higher and 300° C. or lower. 6 . The method for producing a positive electrode active material according to claim 4 , further comprising: washing the Li-containing oxide with water to reduce the sulfur content of the Li-containing oxide.

Citation Information

Patent Citations

  • Non-aqueous electrolyte secondary battery and method of manufacturing the same

    JP2011170994A